2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1031>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability at AAAG repeat sequences in respiratory tract cancers

Abstract: We surveyed the occurrence of novel alleles at microsatellite sequences in non‐small cell lung cancers (NSCLC) using 61 tetranucleotide repeat markers. The presence of at least one new allele, consistent with microsatellite instability (MSI), was observed in 26 of 61 (43%) markers involving 30 of 47 (64%) NSCLC. Twelve of the 26 markers detected new alleles in 2 or more tumors and 11 of these 12 markers contained an AAAG repeat sequence. Using this panel of 12 markers, MSI was detected in 24 of 47 (51%) NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 23 publications
1
60
1
Order By: Relevance
“…Of the 56 subjects in our study, nine (16%) had D7S1482 allele sizes that were a single repeat unit apart but confounding is unlikely since they did not cluster in any specific group (five of 25 cases and six of 31 controls had closely spaced alleles). Our study was limited to the hypermutable marker D7S1482, which has one of the highest levels of mutations in upper aerodigestive tract cancers (Ahrendt et al, 2000;Xu et al, 2001) and the addition of newly identified hypermutable markers will increase the number of possible mutant alleles that can be scored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 56 subjects in our study, nine (16%) had D7S1482 allele sizes that were a single repeat unit apart but confounding is unlikely since they did not cluster in any specific group (five of 25 cases and six of 31 controls had closely spaced alleles). Our study was limited to the hypermutable marker D7S1482, which has one of the highest levels of mutations in upper aerodigestive tract cancers (Ahrendt et al, 2000;Xu et al, 2001) and the addition of newly identified hypermutable markers will increase the number of possible mutant alleles that can be scored.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of microsatellite mutations have been observed in tumours with no known mutations in mismatch repair genes, such as those of the lung, bladder, and head and neck (Mao et al, 1994;Shridhar et al, 1994;Woenckhaus et al, 2003). Mutations in lung cancer are more frequently found in tetranucleotide repeats than in dinucleotide repeats Xu et al, 2001), a phenomenon called Elevated Microsatellite Alterations at Selected Tetranucleotide repeats (EMAST). The underlying mechanism for EMAST is not known, but it is possible that mechanisms other than MMR gene deficiency contribute to the mutations in these tumours, especially in selected microsatellites with AAAG or ATAG repeat units (Ahrendt et al, 2000;Spafford et al, 2001;Xu et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Alterations involving specific tetranucleotide microsatellite DNA sequences, termed "elevated microsatellite alterations at selected tetranucleotide repeats," or EMAST, have not been linked to MMR dysfunction. EMAST has been previously observed in non-small-cell lung, 3,4 skin, 5 ovarian, 6 and bladder cancers. 5,7 The etiology for EMAST is not known, but EMAST has been used as a biomarker for some of these tumors.…”
Section: Introductionmentioning
confidence: 83%
“…[3][4][5][6][7][25][26][27] Several studies could find no link between EMAST and DNA MMR deficiency, the cause of MSI. While the etiology of EMAST is still not clear, general clues point toward some epigenetic relaxation of DNA MMR as one possibility for its cause.…”
Section: Discussionmentioning
confidence: 99%